2020
DOI: 10.1007/s11239-020-02279-1
|View full text |Cite
|
Sign up to set email alerts
|

The administration of rtPA before mechanical thrombectomy in acute ischemic stroke patients is associated with a significant reduction of the retrieved clot area but it does not influence revascularization outcome

Abstract: Both intravenous thrombolysis (IVT) and mechanical thrombectomy (MT) are evidence-based treatments for acute ischemic stroke (AIS) in selected cases. Recanalization may occur following IVT without the necessity of further interventions or requiring a subsequent MT procedure. IVT prior to MT (bridging-therapy) may be associated with benefits or hazards. We studied the retrieved clot area and degree of recanalization in patients undergoing MT or bridging-therapy for whom it was possible to collect thrombus mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 29 publications
1
28
0
Order By: Relevance
“…Although it could be very informative, there is very little published about the influence of IVT on the characteristics of the retrieved clot, such as its general composition and structural organization. Our recent study comparing the size of extracted thrombi showed that bridging-therapy clots were significantly smaller than MT-only clots [16], a finding that is reproduced in the present larger study.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Although it could be very informative, there is very little published about the influence of IVT on the characteristics of the retrieved clot, such as its general composition and structural organization. Our recent study comparing the size of extracted thrombi showed that bridging-therapy clots were significantly smaller than MT-only clots [16], a finding that is reproduced in the present larger study.…”
Section: Discussionsupporting
confidence: 86%
“…There are several studies in the literature comparing final recanalization rate and other clinical outcomes for patients treated with bridging-therapy or MT alone, although there is not yet a clear consensus of opinion [11][12][13][14][15][16]. Nevertheless, bridging-therapy, i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The composition of the clot signifi cantly infl uences the outcome for patients treated with both rtPA and mechanical thrombectomy devices. For example, there is evidence that clots that are red blood cell rich with loose fi brin strands respond best to tPA, which effectively reduces the size of those clots, while other clots are tPA resistant, and need to be removed by mechanical thrombectomy (Rossi et al, 2020). Other recent work in our lab has found that clot composition varies with stroke aetiology (Fig.…”
Section: Stentrieversmentioning
confidence: 86%
“…We also found that IV rtPA administration correlated with a lower rate of VWI. A recent study demonstrated that thrombolysis significantly reduced the clot size, 22 which may help to retrieve the clot without damaging the occluded vessel. Furthermore, a recent three-dimensional scanning electron microscopy analysis of AIS emboli showed that rt-PA treatment resulted in thinning of fibrin fibers and disruption of fibrin network which may explain the reduced clot size.…”
Section: Discussionmentioning
confidence: 99%